2016
DOI: 10.1177/1550059416643193
|View full text |Cite
|
Sign up to set email alerts
|

Lance-Adams Syndrome in the Pretargeted Temperature Management Era

Abstract: Acute posthypoxic myoclonus portends a poor prognosis. Another form of posthypoxic myoclonus, Lance-Adams syndrome, is associated with a better outcome. Differentiating these two entities is important in prognostication and guiding further medical intervention. This can be difficult in the acute setting after hypoxic brain injury but the use of neurophysiologic studies may be helpful. In this article, we present a case of a patient who presented after pulseless electrical activity arrest, underwent targeted te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(50 citation statements)
references
References 72 publications
0
50
0
Order By: Relevance
“…Multiple studies have demonstrated that these EEG patterns, as well as others that signify severe brain injury, predict worse outcomes when found in those with PHM after CRA (4,5,21,(24)(25)(26)29). This was also described in a review by Gupta et al that included 37 articles, of which a number are included in this review (4,11,12,24,27,29, and a number of cases of LAS also described in Freund et al [3]). Other studies have demonstrated the importance of malignant EEG patterns in determining poor prognosis in early PHM but failed to include patients with PHM and more benign neurophysiological findings for comparison (6,11,12,15,17).…”
Section: Neurophysiological Studies May Help Differentiate "Benign" Amentioning
confidence: 99%
See 4 more Smart Citations
“…Multiple studies have demonstrated that these EEG patterns, as well as others that signify severe brain injury, predict worse outcomes when found in those with PHM after CRA (4,5,21,(24)(25)(26)29). This was also described in a review by Gupta et al that included 37 articles, of which a number are included in this review (4,11,12,24,27,29, and a number of cases of LAS also described in Freund et al [3]). Other studies have demonstrated the importance of malignant EEG patterns in determining poor prognosis in early PHM but failed to include patients with PHM and more benign neurophysiological findings for comparison (6,11,12,15,17).…”
Section: Neurophysiological Studies May Help Differentiate "Benign" Amentioning
confidence: 99%
“…However, a more recent study has demonstrated that localization based on the clinical exam is not consistent (4). Though studies have used neurophysiological testing to determine the origin of subtypes of PHM (3,27,35), they have been flawed due to the inconsistent use of EEG-EMG polygraphy and somatosensory evoked potentials (SSEP), both of which have been shown to be the most reliable means of diagnosing cortical myoclonus (3). Therefore, defining cortical and subcortical myoclonus using neurophysiological studies in evaluating early PHM needs further study.…”
Section: Historical Views Of Phmmentioning
confidence: 99%
See 3 more Smart Citations